Genomics driven-oncology: challenges and perspectives - Normanno, Nicola (BMC Cancer, 2015)
Molecularly defined subgroups of tumors characterized by specific driver mutations have been identified in the majority of cancers. The availability of novel drugs capable of targeting signaling pathways activated by genetic derangements has led to hypothesize the possibility to treat patients based on their genomic profile. A clear example is represented by lung adenocarcinoma for which it has been possible to identify driver genetic alterations in approximately 75% of the cases. Among these, RET fusion transcripts are detectable in about 1–2% of lung adenocarcinomas and might represent targets for therapeutic intervention with RET kinase inhibitors. However, a number of issues need to be addressed to make genomics-driven oncology routinely accessible for cancer patients, including: 1) the availability of novel methods in molecular diagnostics that allow a comprehensive molecular characterization of lung tumors starting from a low input DNA/RNA; 2) identification of reliable and reproducible biomarkers of response/resistance to targeted agents; 3) the assessment of the role of tumor heterogeneity in the response to drugs targeting molecular pathways.